An Anchor in Clean Water: The Roles of Anchor Institutions in Managing Great Bay. - Holden, Elisabeth. (2017)
Abstract: Anchor institutions, entities such as colleges and universities, hospitals, military bases, and local businesses that are deeply embedded in a community and could not easily move elsewhere, are increasingly being viewed as partners in social and economic development, particularly in inner city areas. This thesis looks at the roles that anchor institutions can play in environmental initiatives. Using Great Bay in New Hampshire and Maine as a case study and Plum Island Estuary in Massachusetts and Casco Bay in Maine as comparison cases, interviews with relevant stakeholders were used to identify the ways anchor institutions are involved in watershed initiatives. Using the Work Foundation's idea of "anchor coordinators," the roles of umbrella organizations such as the U.S. Environmental Protection Agency's National Estuaries Program partnerships were studied in the ways that they bring together various stakeholders, including anchor institutions, in the watershed. As expected, the University of New Hampshire was found to be an influential anchor institution in Great Bay; this influence came from many departments and various projects. While other anchor institutions participated in various Great Bay protection initiatives, this participation was not found to be widespread. With the government cutting many services and unlikely to provide support to nonprofit watershed protection groups, anchor institutions can help to fill this gap. This study found that local businesses, in particular, may find that their participation in such initiatives creates mutual benefits and helps to create a more advantageous business climate. The study ends with recommendations for anchor institutions and watershed advocates.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Robert Russell.; Committee: Lorlene Hoyt.; Keywords: Water resources management, Urban planning, and Environmental management.